Enhancing firefighter hoods: innovations, challenges, and future directions in PPE design - Hashemian Esfahani, B.; Li, R.; Zhang, M.; Eike, R.; Etemadzadeh, M.; Song, G. (Textile progress, 2025)
This review explores the evolution and challenges of firefighter hoods, emphasizing protection and comfort. Firefighter hoods are critical components of personal protective equipment (PPE), shielding against thermal hazards and airborne particulates. Traditional hoods prioritized thermal insulation but lacked effective particulate filtration, increasing firefighters' exposure to hazardous substances and carcinogens in smoke. Recent advancements, spurred by updates in National Fire Protection Association standards in the US, introduced particulate-blocking hoods that enhance both filtration and thermal protection. However, challenges remain in balancing protection with comfort, as new designs often cause heat stress, mobility limitations, and poor ergonomic fit. Furthermore, real-world testing is crucial to address gaps in evaluating hoods' interaction with other PPE, such as helmets and the self-contained breathing apparatus. This issue of Textile Progress emphasizes the need for comprehensive performance assessments that integrate laboratory-based and real-life testing to optimize hood design and indicates that future research should target ergonomic improvements, enhanced particulate filtration, and contamination risks during donning and doffing. It provides insights for PPE manufacturers, researchers, and fire safety policymakers, to guide the development of hoods that meet safety standards while improving firefighter comfort and operational performance. Such advancements are vital for reducing long-term health risks, including cancer, caused by smoke particulate exposure.